A Discussion Paper: Gender Differences In Protean Career Orientation (PCO) - Teow , Hui Hui; Au , Wee Chan; K Ahmed, Pervaiz (2016)
The trend of protean career is increasingly becoming prominent in turbulent business environment. Individuals are proactively embarking on designing their own career pathways rather than rely on organizational career development activities to cope with the dramatically changing landscape of competitive workplace. This study aims to examine PCO among Gen Yers and how it influences their work behaviors. PCO is a vocational approach in which individuals take charge of their career based on self-directedness and personal values instead of organizational values. Research evidence shows that PCO characteristics resemble much of the working behaviors of Generation Y. Reduction in lifetime employment has triggered Gen Yers to be more alert of the need for continuous skill learning and development; hence they are more likely to proactively plan their own career path. In Malaysia, Gen Yers switch jobs faster than previous generations in the workforce in Malaysia. It is utmost important to seek greater understanding of the factors that determine PCO development and the impact of PCO development on the work behaviors among Gen Yers in Malaysia so as to help inform the best means by which to recruit, engage, and retain them. As compared to men, researchers have found that women are increasingly embracing more self-directed careers while rejecting the traditional long-term employment model. Furthermore, women have been found to engage more often in short‐term career planning using incremental career strategies, a typical characteristic of PCO, while men have more long‐term career goals, which is more typical of traditional career orientation. Most men and women set off with analogous career preferences; yet these preferences deviate over time due to different life situations. Typically, marriage and pregnancy move women off their original career path early in the tenure of their first job. They need to reset their career goals and adopt short‐term strategies that best fit their changing circumstances. Hence, women are more likely to switch jobs for personal or family-related reasons. The research will employ a large-scale questionnaire survey, involving a total number of 400 early career individuals from Generation Y in Malaysia, who have one to three years of work experience.